2014
DOI: 10.25260/ea.14.24.1.0.33
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal activity of volcanic ash against Sitophilus oryzae L. (Coleoptera: Curculionidae) under laboratory conditions

Abstract: This study assessed the acute toxicity and repellence as well as feeding deterrence effect of volcanic ash (VA) on Sitophilus oryzae adults under laboratory conditions. VA resulted in significant adult mortality of S. oryzae. Acute toxicity of the VA was similar to that of commercially available diatomaceous earth DiatomiD ® demonstrating its insecticidal potential. Median lethal concentration values (LC 50 ) obtained were 1610 [1449, 1778] mg/kg for VA and 1046 [916, 1168] mg/kg for DiatomiD ® .Similarly t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This phenomenon holds significant ecological importance, as it can profoundly impact insect populations in the affected area following a volcanic eruption. 46 In this study we took SEM images of individual abdomens of T. castaneum treated with DE and observed that DE particles have direct interaction with the wax layer of its cuticle. Images show a liquid substance composing the wax layer and covering the insect's body that is being absorbed by DE particles (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon holds significant ecological importance, as it can profoundly impact insect populations in the affected area following a volcanic eruption. 46 In this study we took SEM images of individual abdomens of T. castaneum treated with DE and observed that DE particles have direct interaction with the wax layer of its cuticle. Images show a liquid substance composing the wax layer and covering the insect's body that is being absorbed by DE particles (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Another natural occurrence with insecticidal properties, leading to insect mortality through desiccation, is the deposition of volcanic ashes. This phenomenon holds significant ecological importance, as it can profoundly impact insect populations in the affected area following a volcanic eruption 46 …”
Section: Discussionmentioning
confidence: 99%